1979
DOI: 10.1126/science.505015
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Role of Dopamine in the Rat Subthalamic Nucleus and an Adjacent Intrapeduncular Area

Abstract: The subthalamic nucleus, a clinically important component of the extrapyramidal motor system, and a lateral area extending into the peduncle contain catecholamine terminals and dopamine receptors coupled to adenylate cyclase. In addition, dopamine agonists administered in vivo enhance glucose utilization in the region. Thus, neuronal function in this region is directly affected by dopamine and dopaminergic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…The change in SNr Glu levels after dopaminergic denervation may be attributable to an effect restricted to the STN or related structures. Many studies have reported direct dopaminergic innervation of the STN (Brown et al, 1979;Meibach and Katzman, 1979;Campbell et al, 1985;Hassani et al, 1997;Smith et al, 1998), which may control STN neuron activity directly or via presynaptic modulation of neurotransmitter release (Kreiss et al, 1997;Ni et al, 2001;Shen et al, 2003;Cragg et al, 2004). The level of GABA in the SNr also increased in hemiparkinsonian rats.…”
Section: Changes In Basal Glu and Gaba Level Induced By Snc Lesioningmentioning
confidence: 82%
“…The change in SNr Glu levels after dopaminergic denervation may be attributable to an effect restricted to the STN or related structures. Many studies have reported direct dopaminergic innervation of the STN (Brown et al, 1979;Meibach and Katzman, 1979;Campbell et al, 1985;Hassani et al, 1997;Smith et al, 1998), which may control STN neuron activity directly or via presynaptic modulation of neurotransmitter release (Kreiss et al, 1997;Ni et al, 2001;Shen et al, 2003;Cragg et al, 2004). The level of GABA in the SNr also increased in hemiparkinsonian rats.…”
Section: Changes In Basal Glu and Gaba Level Induced By Snc Lesioningmentioning
confidence: 82%
“…Brain regions that receive dopaminergic inputs predominantly from the ventral tegmental area did not show L-dopa-induced increases in glucose utilization to the same degree as those areas that are innervated by the substantia nigra. Because the results obtained with the ['4C]dGlc method are not limited to the primary sites of action of the drug, it is not possible to conclude from these results whether the increases in glucose utilization seen in the subthalamic nucleus and the globus pallidus result from activation of dopaminergic receptors intrinsic to these areas (19)(20)(21) or are a result of dopaminergic activation of the striatum with consequent increased activity in pathways projecting from the striatum to the globus pallidus and subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 98%
“…Hassani ( 1996) has similarly shown that OPe lesions result in only marginally significant STN hyperactivity. In contrast, dopaminergic lesions directly in the STN, which contains D 1 & D2 receptors (Brown et al, 1979; Martres eta!., 1985), result in five times the STN hyperactivity induced by OPe lesions alone (Hassani, 1996). Thus, the GPe-STN projection may be weak relative to the GPe-GPi/SNr projection.…”
mentioning
confidence: 99%